Clinical practice guidelines on newborn hearing screening: A systematic quality appraisal using the AGREE II instrument. (February 2021) - Chorath, Kevin; Garza, Luis; Tarriela, Aina; Luu, Neil; Rajasekaran, Karthik; Moreira, Alvaro
Abstract: Introduction: Several guidelines and consensus statements have been produced and disseminated for the detection and management of newborn hearing loss. However, to date, the quality and methodologic rigor of these screening and management protocols have not been appraised. Objective: To identify and evaluate existing guidelines and consensus statements for the detection and management of neonatal hearing loss. Methods: A comprehensive search of EMBASE, MEDLINE/PubMed, SCOPUS and grey literature sources was conducted until August 2020. The quality of these guidelines was assessed by four independent reviewers using the Appraisal of Guidelines for Research and Evaluation, 2nd edition (AGREE II). Domain scores were considered satisfactory quality if they scored >60%, and intraclass correlation coefficients (ICC) were calculated to assess agreement among the appraisers. Results: Twelve guidelines were assessed for critical evaluation. Only two guidelines were classified as 'high quality', and the remaining were 'average' or 'low quality'. The 'Scope and Purpose' domain achieved the highest mean score (91.3% ± 5.8%), and lowest was 'Rigor of Development' (35.8% ± 19.1%). ICC analysis showed good to very good agreement across all domains (0.63–0.95). Conclusion: These findings highlight the variability in methodologic quality of guidelines and consensus statement for the detection and management of neonatal hearing loss. These results may help to improve the reporting of future guidelines and guide the selection and use of these guidelines in clinical practice.